Telemonitoring of elderly with hypertension and type 2 diabetes at the primary care level: Protocol for a multicentric randomized controlled pilot study - Mihevc Matic; Zavrnik Črt; Mori Lukančič Majda; Virtič Tina; Prevolnik Rupel Valentina; Petek Šter Marija; Klemenc Ketiš Zalika; Poplas Susič Antonija (Sciendo, 2022)
Arterial hypertension (AH) and type 2 diabetes (T2D) represent a significant burden for the public health system, with an exceptionally high prevalence in patients aged ≥65 years. This study aims to test the acceptability, clinical effectiveness, and cost-effectiveness of telemonitoring in elderly patients with AH and T2D at the primary care level.